A critical assessment of information technology adoption: technical, organisational and personal perspectives. (2nd September 2010) - Daim, Tugrul; Basoglu, Nuri; Tanoglu, Ilda
In today's rapidly changing competitive environment, information technology (IT) within an organisation is continuously improved, driven by external push of technological advances and internal pull of increasing organisational needs. In order to achieve the greatest return on IT investment, the diffusion process of IT within the organisation should be examined carefully. This study aims to explore the effects of technical, organisational and personal characteristics on the diffusion of different information technologies within organisations, and to discover the relationship between the diffusion and infusion of these technologies and the effectiveness, efficiency and productivity of managerial decision making processes. Based on a thorough review of theoretical background and prior empirical studies in the area, an integrated research framework concerning IT diffusion context has been developed and tested via a survey applied on individuals from different organisations. Findings suggest that the antecedents of the diffusion patterns vary for different types of information technologies.